Etude des algorithmes d'égalisation des canaux de communications numériques - ABDELLATIF, BARMAKI (Université Mohamed Boudiaf - M’sila Faculté de technologie, 2016)
The purpose of this work is the study of the equalization techniques for digital communication channels. Two equalizers are presented, linear and non-linear namely the transverse linear equalizer (LTE) and the decision feedback equalizer (DFE). The simulations results have shown the performance of these equalizers in terms of constellation of the equalized symbols and the mean square error( MSE) for different communication channels. The linear equalizer LTE works best for linear low distortion channels its performance degrades significantly, for severs and nonlinear channels. The use of the non-linear equalizer DFE has exhibited consistent improvements in performance for all the considered channels.
Keywords: Egalisation adaptative; Transmission numérique; Filtrage adaptatif; Canaux de transmission